2001
DOI: 10.1053/euhj.2000.2546
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of sinus rhythm after electrical cardioversion of persistent atrial fibrillation. Sotalol vs bisoprolol

Abstract: This study demonstrates that sotalol (160 mg x day(-1)) and bisoprolol (5 mg x day(-1)) are equally effective in maintaining sinus rhythm. Because of the side effects of sotalol, bisoprolol seems to be advantageous for maintenance of sinus rhythm after cardioversion of atrial fibrillation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
8

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(41 citation statements)
references
References 22 publications
1
32
0
8
Order By: Relevance
“…Various beta blockers have shown moderate but consistent efficacy to prevent AF recurrence or reduce the frequency of paroxysmal AF, comparable to conventional antiarrhythmic drugs. [583][584][585][586] One placebo-controlled study 583 of 394 patients with persistent AF found a lower risk of early recurrence after cardioversion and slower ventricular response with sustainedrelease metoprolol than placebo. 583 Two studies found atenolol 587 and bisoprolol 584 as effective as sotalol and better than placebo in reducing the frequency and duration of paroxysmal AF and in reducing the probability of relapse after cardioversion, but proarrhythmic events occurred more often during treatment with sotalol.…”
Section: Agents With Proven Efficacy To Maintain Sinus Rhythmmentioning
confidence: 99%
“…Various beta blockers have shown moderate but consistent efficacy to prevent AF recurrence or reduce the frequency of paroxysmal AF, comparable to conventional antiarrhythmic drugs. [583][584][585][586] One placebo-controlled study 583 of 394 patients with persistent AF found a lower risk of early recurrence after cardioversion and slower ventricular response with sustainedrelease metoprolol than placebo. 583 Two studies found atenolol 587 and bisoprolol 584 as effective as sotalol and better than placebo in reducing the frequency and duration of paroxysmal AF and in reducing the probability of relapse after cardioversion, but proarrhythmic events occurred more often during treatment with sotalol.…”
Section: Agents With Proven Efficacy To Maintain Sinus Rhythmmentioning
confidence: 99%
“…Both showed a similar level of P-AF suppression. Plewan, et al 23) compared the suppression of P-AF recurrence in persistent AF patients who underwent electrical defibrillation, and demonstrated that bisoprolol administration had a similar effect to that of sotalol administration in terms of suppressing P-AF recurrence. Furthermore, they concluded that administration of bisoprolol was more effective than administration of sotalol because of the lower incidence of side effects observed in the patients treated with bisoprolol.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, relatively few patients were treated with antidysrhythmics (Sotalol 15%, b-blocker 22% and verapamil 6%) which may account for the low proportion of patients in sinus rhythm at 1-month follow-up. Earlier studies have shown a tendency for an increase in the proportion of patients remaining in sinus rhythm after cardioversion when treated with b-blockers [15,16].…”
Section: Discussionmentioning
confidence: 99%